SEVERE VASCULAR CALCIFICATION IN PERIPHERAL ARTERIAL DISEASE: IS THERE A LIMIT TO REVASCULARIZATION? - Mendes, Daniel (2018)
Vascular calcification is associated with a worsening of the ischemia categories in patients with peripheral arterial disease independently and represents a huge challenge in both endovascular treatment and revascularization surgery. We present a case report of a patient with multiple cardiovascular risk factors and with risk factors for calcification (diabetes and chronic kidney disease), with critical ischemia, adequately treated with a popliteal-pedous bypass.